After distributing the terms (2x + 3) (4x – 5), you get a new expression of the form
ax+ bx + c
What is the value of a?
What is the value of b?
What is the value of c?

Respuesta :

Answer:

Value of a = 8

Value of b = 2

Value of c = - 10

Step-by-step explanation:

[tex](2x + 3)(4x - 5)[/tex]

[tex] = > 2x(4x - 5) + 3(4x - 5)[/tex]

[tex] = > 8 {x}^{2} - 10x + 12x - 15[/tex]

[tex] = > 8 {x}^{2} + 2x - 10[/tex]

As per the general form of a quadratic eqn. [tex]a {x}^{2} + bx + c[/tex]

Value of a = 8

Value of b = 2

Value of c = - 10

ACCESS MORE